Device and method for indirect measurement of physical property of rock and soil. - Omar, Husaini (2003)
The present invention relates to a device and method for measurement of tensile strength of materials, especially for indirectly measuring the tensile strength of weak rock and hard soil. The probe of the measuring device comprises a cylindrical body with an expandable flexible membrane designed to apply a uniform pressure to the walls of a cavity, such as a bore hole. There is no need to cut a core specimen to a particular shape for measurement, thus making it an attractive option for measurement of weakly bonded rock and hard soil.